Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4048/jbc.2015.18.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Safety Results of Docetaxel-(Taxotere®)-Based Chemotherapy in Early Breast Cancer Patients of Asia-Pacific Region: Asia-Pacific Breast Initiative II

Abstract: PurposeThe goal of this registry was to collect patient characteristics and safety data from patients from the Asia-Pacific region with early breast cancer receiving adjuvant chemotherapy containing docetaxel (Taxotere®).MethodsThis registry was open-label, international, longitudinal, multicenter, and observational in design and included a prospective group of consecutive early breast cancer patients with an intermediate-to-high risk of recurrence being treated with various docetaxel-based (anthracycline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The occurrence of abnormal total- and LDL-cholesterol among premenopausal patients has been attributed to chemotherapy-induced ovarian dysfunction [ 29 31 ]. The observation from a recent study lends support to this by showing that peri-menopausal patients undergoing taxane-based adjuvant chemotherapy had the largest change in lipids profiles when compared to pre- or post-menopausal patients, implicating that transition in hormone status may play a role [ 32 ]. Tamoxifen has been well-reported to lower total- and LDL-cholesterol [ 33 36 ] as early as 3 months after treatment initiation [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of abnormal total- and LDL-cholesterol among premenopausal patients has been attributed to chemotherapy-induced ovarian dysfunction [ 29 31 ]. The observation from a recent study lends support to this by showing that peri-menopausal patients undergoing taxane-based adjuvant chemotherapy had the largest change in lipids profiles when compared to pre- or post-menopausal patients, implicating that transition in hormone status may play a role [ 32 ]. Tamoxifen has been well-reported to lower total- and LDL-cholesterol [ 33 36 ] as early as 3 months after treatment initiation [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 98%
“…Anthracycline plus taxanes had a greater impact on serum lipids than taxanes. 49 It was obvious that anthracyclines plus taxanes were more likely to cause dyslipidemias than anthracyclines, which was more likely to cause dyslipidemias than taxanes. Anthracyclines had a greater effect on TG and HDL-C, while taxanes had a greater effect on TC and LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of three phase III studies in EBC showed that sequential administration of anthracyclines and taxanes provides a significant improvement in in OS and DFS over combination dosing (35). In contrast, a long-term followup from the Breast Cancer International Research Group (BCIRG)-005 study suggested there is no difference in OS or DFS between TAC or AC-T, although TAC was associated with higher rates of febrile neutropenia, and AC-T with higher rates of myalgia, hand-foot syndrome, and neuropathy (28). Nonetheless, sequential administration of anthracyclines and taxanes is recommended by treatment guidelines (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…In women with nodepositive EBC, a sequential docetaxel regimen [doxorubicin and cyclophosphamide followed by docetaxel (AC-T)] was associated with superior survival outomes compared with concurrent doxorubicin and docetaxel (TA) and concurrent TAC (27). However, data from a 10-year follow-up of a further study revealed no long-term difference in DFS or overall survival (OS) with sequential versus concurrent docetaxel (28).…”
Section: Introductionmentioning
confidence: 99%